The Effect of Alum, Tunjung, and Betel Lime Mordants on Ecoprinting Insulin Leaves Using Combined Pounding and Blanket Techniques on Yamaha Silk Dyed with Gambir Extract - Miftahul Jannah; Adriani Adriani; Sri Zulfia Novrita; Samuel Marthin Pradana (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2025)
The rapid growth of the textile industry has made it one of the largest contributors to environmental pollution, particularly through waste generated during the large-scale color refinement of synthetic textiles. A sustainable alternative to mitigate this issue is the use of eco-friendly textile dyeing methods such as ecoprint. This study aims to examine the effects of three mordant types—alum, ferrous sulfate (tunjung), and betel lime—on the ecoprint results of insulin leaves (Smallanthus sonchifolius) applied to Yamaha Silk fabric using a combination of pounding and blanket techniques. Employing a quantitative experimental method, the research used Yamaha Silk fabric ecoprinted with insulin leaves and gambier extract, treated with pre-mordanting. Primary data were collected from evaluations by 15 panelists (three lecturers and twelve students) through a questionnaire assessing various indicators. Data were analyzed using the Friedman K-Related Samples test via SPSS. The findings revealed that the color outcomes (hue) varied by mordant: without mordant produced a Golden Sundance color; alum resulted in Soft Brown; tunjung yielded Olive; and betel lime produced Dark Brown. Regarding motif clarity, alum mordant achieved the highest clarity, followed by no mordant, betel lime, and tunjung. A significant difference was observed among treatments for motif clarity (Asymp. Sig = 0.005 < 0.05). In terms of color fastness, after one washing, alum mordant maintained the most stable color, followed by tunjung and betel lime. Significant differences in color fastness were also recorded after two and three washings (p = 0.013, 0.036, and 0.004, respectively; all < 0.05). Overall, the use of alum mordant produced the best ecoprinting results on Yamaha Silk, yielding superior color intensity, motif clarity, and wash fastness. These results suggest that the ecoprinting technique, particularly with alum mordant, holds strong potential as an environmentally friendly alternative in sustainable textile production.